Comprehensive Care Program On Pain, Functional Recovery, Nutritional Status And Occurrence Of Complication Among Patient With Hip Surgery - T.VIJAYAPRIYA MSC (N),; DR.A.RATHINAVEL MS.Mch, Ph.D,; DR. MANGALAGOWRI Ph.D (N),; DR.S.J.NALINI MSC (N), PH.D, (International Journal of Pharma and Bio Sciences, 2015)
The aim of this study was to compare the effects of a comprehensive care program with those of usual care for the patient who undergone hip surgery. True experimental design (Two group post test only design) was selected for the study. The participants were 30 subjects with hip surgery from selected hospitals at Madurai. Based on simple random sampling method, the samples were divided into experimental and control group (15 in each group). The Comprehensive care program was given to experimental group and the routine care was given to a control group. The post test was assessed for both groups. The results found that the patient with hip surgery who receive comprehensive care program achieved good pain control, improved knowledge on functional recovery, nutrition and absence of complication than usual care group (p<0.05).The study concludes that the comprehensive care program ,when administered to the patient with hip surgery, has beneficial effect on post operative outcome.